Improving hemocompatibility in tissue-engineered products employing heparin-loaded nanoplatforms - Nima Beheshtizadeh; Mahsa Mohammadzadeh; Mehrnaz Mostafavi; Amir Abbas Seraji; Faezeh Esmaeili Ranjbar; Seyedeh Zoha Tabatabaei; Robabehbeygom Ghafelehbashi; Maede Afzali; Farshad Lolasi (Elsevier, 2024)
The enhancement of hemocompatibility through the use of nanoplatforms loaded with heparin represents a highly desirable characteristic in the context of emerging tissue engineering applications. The significance of employing heparin in biological processes is unquestionable, owing to its ability to interact with a diverse range of proteins. It plays a crucial role in numerous biological processes by engaging in interactions with diverse proteins and hydrogels. This review provides a summary of recent endeavors focused on augmenting the hemocompatibility of tissue engineering methods through the utilization of nanoplatforms loaded with heparin. This study also provides a comprehensive review of the various applications of heparin-loaded nanofibers and nanoparticles, as well as the techniques employed for encapsulating heparin within these nanoplatforms. The biological and physical effects resulting from the encapsulation of heparin in nanoplatforms are examined. The potential applications of heparin-based materials in tissue engineering are also discussed, along with future perspectives in this field.